Paired photoelectrocatalytic reactions of glucose driven by a photoelectrochemical fuel cell with assistance of methylene blue. (20th August 2016) - Zhao, Qianwen; Li, Zhen; Deng, Qiang; Zhu, Licai; Luo, Suilian; Li, Hong
Graphical abstract: Highlights: Reversible colorimetric reactions can be controlled by turning on and off UV light. Paired redox reactions of GLU are driven by photoelectrochemical fuel cells. A linear current response to GLU (0.5-2.0 mol L −1 ) appears in two compartments. MB is required to mediate the paired photoelectrocatalytic reactions of GLU. The assembled cell shows IPCE of 27.2% (365 nm), and P max / P in of 13.1% (UV). Abstract: This paper reports the paired photoelectrocatalytic reactions of glucose (GLU) by capturing the photogenerated electrons and holes from ultraviolet (UV)-excited TiO2 nanoparticles (NPs) with the assistance of methylene blue (MB) in neutral media. The blue MB in a mixed system containing TiO2 NPs and GLU can rapidly capture the photogenerated electrons upon UV irradiation to form colorless leuco methylene blue (LMB), which is recovered in the dark, representing reversible colorimetric reactions controlled by turning on and off UV light. More interestingly, while employing TiO2 /ITO photoanode and ITO cathode to assemble a UV-excited photoelectrochemical fuel cell, GLU existing in anode and cathode compartments can act as reducing and oxidizing agents to involve the paired photoelectrocatalytic reactions promoted by the MB/LMB-based reversible redox system. The cell current shows a linear response to GLU between 0.5 and 2.0 mol L −1 . Meanwhile, while adding 2.0 mol L −1 GLU and 2.0 mol L −1 GLU/10.0 mmol L −1 MB to the anode and cathode compartments, respectively, the assembled photoelectrochemical fuel cell shows open-circuit photovoltage of 0.828 V, short-circuit photocurrent density of 29.2 μA cm −2, maximum power density of 7.2 μW cm −2 at 0.345 V under UV irradiation of 55 μW cm −2 .